Origin and Evolution of H1N1/pdm2009: A Codon Usage Perspective - Guo, Fucheng; Yang, Jinjin; Pan, Junbin; Liang, Xianghui; Shen, Xuejuan; Irwin, David M.; Chen, Rui-Ai; Shen, Yongyi (Frontiers in Microbiology, 2020)
The H1N1/pdm2009 virus is a new triple-reassortant virus. While Eurasian avian-like and triple-reassortant swine influenza viruses are the direct ancestors of H1N1/pdm2009, the classic swine influenza virus facilitate the spectrum of influenza A diversity in pig population when the reassortant events occurred during 1998 to April 2009. The factors that facilitate the final formation of this gene constellation for H1N1/pdm2009 virus from this complex gene pool remain unknown. Since a novel successful virus should efficiently replicate and transmit in their hosts, in this study, we estimated the adaptability of the codon usage patterns of the pool of genes from these lineages of swine influenza viruses to the human expression system. We found that the MP and NA genes of Eurasian avian-like swine influenza viruses, and the PB2, PB1 and PA genes of triple-reassortant swine influenza viruses were best adapted to the human codon usage pattern. As these genes participated in the development of H1N1/pdm2009, they might help in viral replication and strengthen its competitiveness during its emergence. After its emergence in the human population, a gradual optimization of codon usage patterns between 2009 and 2019 to the human codon usage for the H1N1/pdm2009 genes was detected. This reveals that ongoing adaptive evolution, after its original incursion, occurred to further increase the adaptability of overall gene cassette to human expression system.